East southeast exterior view of John Bunyan's Meeting House, Zoar Street, Gravel Lane, Southwark - Unknown (Tufts Archival Research Center, 2008)
With a plan of the site. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.